Expression of T‐cell immunoglobulin and immunoreceptor tyrosine‐based inhibitory motif domain on CD4+ T cells in patients with atopic dermatitis. Issue 1 (7th November 2018) - Kurita, Miki; Yoshihara, Yuki; Ishiuji, Yozo; Chihara, Mami; Ishiji, Takaoki; Asahina, Akihiko; Yanaba, Koichi
Abstract: The T‐cell immunoglobulin and immunoreceptor tyrosine‐based inhibitory motif domain (TIGIT) is a co‐inhibitory receptor mainly expressed on T cells. Although TIGIT plays an important role in various autoimmune diseases, its role in atopic dermatitis (AD) remains unclear. In this study, we examined the expression levels of TIGIT and their association with clinical features in patients with AD. TIGIT expression on CD4 + T cells, central memory T cells, effector memory T cells and regulatory T cells was determined by flow cytometry. CD4 + T cells exhibited enhanced TIGIT expression in patients with AD compared with healthy individuals. In particular, effector memory T cells and regulatory T cells, but not central memory T cells, exhibited higher TIGIT expression in patients with AD than in healthy individuals. The frequency of TIGIT + cells among CD4 + T cells was significantly increased in patients with mild AD compared with healthy individuals, while decreased in patients with severe AD. Consistently, the frequency of TIGIT + cells among CD4 + T cells was negatively correlated with both serum thymus and activation‐regulated chemokine levels and immunoglobulin E levels in patients with AD. Furthermore, TIGIT expression on CD4 + T cells inhibited cell proliferation in patients with AD. These results suggest that TIGIT expression on CD4 + T cells in patients with AD may be increased to suppress chronic cutaneous inflammation. Moreover, TIGIT expression may be impaired in a subset of patients with AD, leading to a deterioration of skin inflammation. Our study may provide new insight into a TIGIT pathway‐based therapeutic approach for AD.